3D field ion microscopy and atom probe tomography techniques for the atomic scale characterisation of radiation damage in tungsten - Dagan, M (2016)
In this work, new reconstruction and analysis methods were developed for 3D field ion microscopy (FIM) data, motivated by the goal of atomic scale characterisation of radiation damage for fusion applications. A comparative FIM/ atom probe tomography (APT) study of radiation damage in self-implanted tungsten revealed FIM advantages in atomistic crystallographic characterisation, able to identify dislocations, large vacancy clusters, and single vacancies. While the latter is beyond the detection capabilities of APT, larger damage features were observed indirectly in APT data via trajectory aberrations and solute segregation. An automated 3DFIM reconstruction approach was developed to maintain reliable, atomistic, 3D insights into the atomic arrangements and vacancies distribution in ion-implanted tungsten. The new method was utilized for the automated ‘atom-by-atom’ reconstruction of thousands of tungsten atoms yielding highly accurate reconstructions of atomically resolved poles but also applied to larger microstructural features such as carbides and a grain boundary, extending across larger portions of the sample. Additional tools were developed to overcome reconstruction challenges arising from the presence of crystal defects and the intrinsic distortion of FIM data. Those were employed for the automated 3D mapping of vacancies in ion-implanted tungsten, analysing their distribution in a volume extending across 50nm into the depth of the sample. The new FIM reconstruction also opened the door for more advanced analyses on FIM data. It was applied to the preliminary studies of the distortion of the reconstructed planes, found to depend on crystallographic orientation, with an increased variance in atomic positions measured in a radial direction to the centre of the poles. Additional analyses followed the subtle displacements in atomic coordinates on consecutive FIM images, to find them affected by the evaporation of atoms from the same plane. The displacements were found to increase with size as the distance to the evaporated atom decreased, and are likely to be the result of a convolution between image gas effects, surface atoms relaxation, and charge re-distribution. These measurements show potential to probe the dynamic nature of the FIM experiment and possibly resolve contributions from the different processes effecting the final image. Finally, APT characterisation was performed on bulk and pre-sharpened needles to determine the effect of sample’s geometry on the resulting implantation profiles, and the extent to which pre-sharpened needles could be employed in radiation damage studies. While the ions depth profiles in needles were not found within a good match to SRIM simulations, the damage profiles exhibited closer agreement. Further, the concentration of implanted ions in bulk samples was found significantly higher than in the respective needle implanted samples, with excessive loss found for the light ion implantation.